Legal Analysis of the Differences between the Democratic System in Indonesia and Other Countries - Mukhtasor Mukhtasor; Arpangi Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This research is motivated by the significant differences between Indonesia’s democratic system and those of other countries, each shaped by distinct constitutional traditions. Indonesia’s democracy, grounded in Pancasila and the 1945 Constitution, exhibits unique characteristics that require deeper examination to understand how constitutional norms regulate governmental authority, public participation, and the relationship among state institutions. The objective of this research is to analyze the characteristics of Indonesia’s democracy, compare it with other democratic systems, and assess the juridical implications for governance administration. This study employs a normative juridical method using statutory, conceptual, and comparative approaches. The analysis is conducted through an examination of the 1945 Constitution, legislation related to democratic governance, and the constitutions of selected countries for comparison. The comparative approach helps identify fundamental differences between Indonesia’s presidential system and the parliamentary, federal, or semi-presidential systems of other nations. The findings reveal that differences in democratic systems have direct implications for checks and balances, the central–regional relationship, public participation mechanisms, and the capacity of representative institutions to supervise the executive. Comparative insights indicate that Indonesia must strengthen oversight regulations, clarify regional authority, and enhance legislative transparency to maintain governmental stability while upholding constitutional democratic principles.